A matter of time? Challenging and hindering effects of time pressure on work engagement. Issue 3 (3rd July 2018) - Baethge, Anja; Vahle-Hinz, Tim; Schulte-Braucks, Julia; van Dick, Rolf
ABSTRACT: The aim of our research was to test time-exposure effects of time pressure as a stressor typically considered to be a challenge, rather than a hindrance stressor. We examined the within- and between-person effects of time pressure on work engagement in two diary/panel studies with employees using intervals of five days and three weeks, respectively (Study 1, n  = 350, and n  = 357, respectively) and six to eight weeks (Study 2, n  = 238). We assumed that it is a matter of time whether time pressure acts as a challenge (under short-term exposure) or as a hindrance stressor (under long-term exposure). We found significant positive within-person effects of time pressure on work engagement when controlling for strain in the daily and weekly diary assessment (Study 1), but a significant negative within-person effect in the six to eight weeks' assessment (Study 2). The between-person effects were significant and negative in all studies. Although a short-term increase can be beneficial for a certain time, stable and long-time exposure of time pressure does rather reduce work engagement. Thus, employers should not keep time pressure permanently high to motivate their employees. However, short-term increases of time pressure (e.g. before a deadline) may serve as a motivating factor.